2013
DOI: 10.3390/molecules18010574
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Different Co-Antioxidants on the Photochemical- and Functional-Stability of Epigallocatechin-3-gallate in Topical Creams Exposed to Simulated Sunlight

Abstract: The catechin (−)-epigallocatechin-3-gallate (EGCG) exhibits high antioxidant activity and it has been reported to provide protection of the skin against damage induced by solar UV radiation. However, EGCG is highly unstable under sunlight. The present study aimed to compare the effectiveness of the co-antioxidant agents vitamin E, butylated hydroxytoluene, vitamin C and α-lipoic acid for their potential to protect the catechin from photochemical degradation. Model creams (oil-in-water emulsions) containing EGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 38 publications
2
57
1
2
Order By: Relevance
“…Furthermore, Scalia et al (Scalia et al, 2013) suggested that co-treatment with vitamin C and lipoic acid significantly reduces the photodegradation of EGCG and preserves its antioxidant activity under UV irradiation. Therefore, the application of EGCG with co-antioxidant agents such as vitamin C and lipoic acid should be considered in topical treatments for UV irradiation-induced skin photoaging.…”
Section: Antioxidant Effectsmentioning
confidence: 98%
“…Furthermore, Scalia et al (Scalia et al, 2013) suggested that co-treatment with vitamin C and lipoic acid significantly reduces the photodegradation of EGCG and preserves its antioxidant activity under UV irradiation. Therefore, the application of EGCG with co-antioxidant agents such as vitamin C and lipoic acid should be considered in topical treatments for UV irradiation-induced skin photoaging.…”
Section: Antioxidant Effectsmentioning
confidence: 98%
“…After irradiation, the reduction in the antioxidant capacity of the formulation with EGCG was lower (21.8%) than degradation of extension (76.9%), suggesting the formation of photoproducts with antioxidant properties. Among the evaluated antioxidants, α-lipoic acid showed the most positive results, proving to be an effective antioxidant co-agent for stabilization of the (-)-epigallocatechin-3-gallate in dermatological products for photoprotection of the skin because it reduced most significantly the degradation of EGCG and stabilized better antioxidant activity of the formulation, down only 1.4% of the activity (Scalia et al, 2013).…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%
“…Meanwhile, ALA exhibits poor water solubility and low stability under UV radiation [10]. Interestingly, ALA was an effective co-antioxidant agent for the stabilization of EGCG from solar simulator [11]. Moreover, previous studies have revealed that the synergistic effect of EGCG and ALA in vivo [8].…”
Section: Introductionmentioning
confidence: 97%